Desecuritization of cannabis in the United States: drug policy reform from the ground-up - Nunes, Natália da Silva (2023)
This PhD dissertation examines drug policies in the United States and explores its dichotomy between domestic and federal policies. Although marijuana is legal under some states laws, it remains illegal under federal law creating all sorts of hurdles, from taxing to banking to interstate commerce. The US has been the driving force behind the establishment of the international drug control regime and has historically been its main enforcer. However, as the failures of the punitive and prohibitive drug control paradigm, both nationally and internationally, became increasingly acute, the consensus around the model began to break. Popular support for reforms led to changes in the scenario, legislation painted the US map in green for recreational use of marijuana in now more than twenty states. To understand this process, we use the international security studies theory of Securitization and Desecuritization. This approach shows how discourse and the concept of threats shape security responses, in this case, how the states have dealt with drug issues. I ask: how the prohibition regime leader is now rearticulating the drug issue from securitization to Desecuritization? How is this process taking place? Who are the actors involved? What is the impact of the domestic policies on the federal ones? I explore in detail two case-studies: the state of California and the state of Texas, comparing how the drug issue is perceived and their laws were made. My findings show that the securitization process of drugs in the US was led by the government, top-down; while the Desecuritization process was mostly performed by civil society, from the ground-up. Moreover, I found that beyond American federalism and bipartisan system, marijuana reforms are possible due to public support, access to ballot initiatives and local leadership.